En defensa de la justicia: explicando la improbable inaplicación judicial del indulto y derecho de gracia del condenado por graves violaciones a los derechos humanos Alberto Fujimori - de Belaunde de Cárdenas, Javier Alonso (2020)
Alberto Fujimori, Peruvian ex-president and perpetrator of human rights violations, was released from prison due to a presidential pardon in 2017. He was also granted immunity from prosecution. Although the political branches and the majority of the population supported these measures, as shown by public opinion polls, within months domestic courts overturned them completely, relying on standards set by the Inter-American Court of Human Rights. This is the most unlikely result, comparatively. The article examines what could explain this pro human rights accountability behaviour in the judiciary. It argues that the outcome could be the product of two processes initialised during the Peruvian transition: Judicial empowerment (independence and power gains) and legal culture shift from positivism to neo-constitutionalism. Both are defined and analysed with reference to transitional justice and socio-legal studies scholarship. The article further seeks to identify the conditions under which Inter-American conventionality control doctrine could have a strong domestic impact.